Characterization of Chlamydomonas Ribulose-1,5-bisphosphate carboxylase/oxygenase variants mutated at residues that are post-translationally modified - Rasineni, Girish Kumar; Loh, Pek Chin; Lim, Boon Hoe (Biochimica et biophysica acta. General subjects, 2017)
Ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco) is the chloroplast enzyme that fixes CO2 in photosynthesis, but the enzyme also fixes O2, which leads to the wasteful photorespiratory pathway. If we better understand the structure-function relationship of the enzyme, we might be able to engineer improvements. When the crystal structure of Chlamydomonas Rubisco was solved, four new posttranslational modifications were observed which are not present in other species. The modifications were 4-hydroxylation of the conserved Pro-104 and 151 residues, and S-methylation of the variable Cys-256 and 369 residues, which are Phe-256 and Val-369 in land plants. Because the modifications were only observed in Chlamydomonas Rubisco, they might account for the differences in kinetic properties between the algal and plant enzymes. Site-directed mutagenesis and chloroplast transformation have been used to test the essentiality of these modifications by replacing each of the residues with alanine (Ala). Biochemical analyses were done to determine the specificity factors and kinetic constants. Replacing the modified-residues in Chlamydomonas Rubisco affected the enzyme's catalytic activity. Substituting hydroxy-Pro-104 and methyl-Cys-256 with alanine influenced Rubisco catalysis. This is the first study on these posttranslationally-modified residues in Rubisco by genetic engineering. As these forms of modifications/regulation are not available in plants, the modified residues could be a means to modulate Rubisco activity. With a better understanding of Rubisco structure-function, we can define targets for improving the enzyme. •Chlamydomonas Rubisco has four posttranslational modifications not observed in other species.•Replacing the modified-residues in Chlamydomonas Rubisco negatively affects function.•The modified-residues could be a means to modulate Rubisco activity.•With a better understanding of Rubisco structure-function, we can define targets for improving the enzyme.